Preparedness for Academic Excellence in Higher Education through BPO - Hamal, Balendu (Medha: A Multidisciplinary Journal, 2023)
COVID-19 Pandemic has been a very serious problem worldwide. It has damaged all economic germinate areas. Also the Nepalese higher education field has been disturbed. Our teaching and learning methodologies are conventional. Additionally, politicians, policy makers do not want to change and adopt new concept with high-tech. Academicians and administrative staff are thinking positively, but those people are not techno friendly so that in crucial time they are resistant to change. Still, these situations create a big opportunity in Nepal; thus, the higher education sector would apply the BPO technique to provide quality education for their students with low budgets. This study focuses on how to professionally manage teaching and learning service delivery over the public or private networks to help students use ICT effectively and efficiently. It is a new concept in the education field of Nepal, but developed countries have practiced from last decade. The 21st century is more competitive, and challenges and opportunities come together, where we live in a boundary-less small village appropriate to the speedy of ICT. Through the use of outsourcing (offshoring), stakeholders can take more benefits than the usual method. Especially BPO procedure helps teachers, students, and organizations to meet international standards throughout academic excellence and smooth operation.